FAKTOR YANG MEMENGARUHI EKSPRESI EMOSI ANAK DENGAN INDIKASI DISLEKSIA YANG MENJALANI TERAPI SENI EKSPRESIF - Irene, Joe; Tiatri, Sri; Mar’at, Samsunuwiyati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2020)
Limited reading and writing abilities in children with dyslexia make it difficult for them to succeed academically when given a typical learning method. In addition to difficulties in the academic field, children with dyslexia also experience difficulties in their psychosocial functioning. Emotional problems become